2021
DOI: 10.1021/acs.cgd.1c00358
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Hydration Differences in Cocrystal Polymorphs: High-Resolution X-ray Investigation of Caffeine–Glutaric Acid Cocrystals

Abstract: Two polymorphic forms of caffeine (CAF)–glutaric acid (GLU) cocrystals have been studied via high-resolution X-ray crystallography and Bader’s quantum theory of atoms in molecules (QTAIM). For both the monoclinic, 1, and triclinic, 2, systems the experimental charge density distributions of the 1:1 ratio of CAF and GLU polymorphs have been determined and compared. Previous studies have determined that 1 is less stable than 2, in relative humidity (RH) testing. A topological analysis of the electron density dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 48 publications
(141 reference statements)
0
16
0
Order By: Relevance
“…A study by Hawkins et al showed an underestimation of the EXP ∇ 2 ρ bcp compared to the theoretical value but this did not affect ρ bcp of the internal covalent bond, hydrogen bond or synthon. 12 As such the derived products of hydrogen bond strength were not affected in this environment. 12 Similarly, the study of Wagner et al which was at a higher level of experimental resolution found the ∇ 2 ρ bcp around the nitrogen species had near identical ρ bcp but much lower ∇ 2 ρ bcp compared to the theoretical, which also did not affect the derived hydrogen bond strength.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…A study by Hawkins et al showed an underestimation of the EXP ∇ 2 ρ bcp compared to the theoretical value but this did not affect ρ bcp of the internal covalent bond, hydrogen bond or synthon. 12 As such the derived products of hydrogen bond strength were not affected in this environment. 12 Similarly, the study of Wagner et al which was at a higher level of experimental resolution found the ∇ 2 ρ bcp around the nitrogen species had near identical ρ bcp but much lower ∇ 2 ρ bcp compared to the theoretical, which also did not affect the derived hydrogen bond strength.…”
Section: Resultsmentioning
confidence: 83%
“…For example, in CAF:GLU polymorphs there was a variation of just a single hydrogen bond and this was the cause of the slower hydration rates seen between polymorphs. 12 This suggests that a comparison of the topological features in hydrogen bonding between reactants and products may reveal why THEO:MA formation did not enhance the hygroscopic profile of THEO. This review can be done in many ways, the ability to identify hydrogen bonds and other interactions is a now standard procedure, e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…16–19 Thus, it is necessary to carry out more research on cocrystal polymorphism including synthesis strategies, solid-state characterization, performance evaluation and phase transition processes, which is of great significance for better application of cocrystallization technology in the pharmaceutical field. 20–25…”
Section: Introductionmentioning
confidence: 99%